RELEVANSI STRATEGI PAIKEM PADA PEMBELAJARAN IPA MADRASAH IBTIDAIYAH: STUDI KEPUSTAKAAN - Putri Aulia; Yuniar Fahmi Lathif; Muhammad Syaiful Munir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the theoretical and practical relevance of the Active, Innovative, Creative, Effective, and Joyful Learning (PAIKEM) strategy in Natural Sciences (IPA) subjects at Madrasah Ibtidaiyah (MI). This research is motivated by the gap between the ideal conditions of inquiry-based science learning and the reality of the domination of conventional methods in the field, which results in students' low conceptual understanding and learning motivation. The research method used is library research with a qualitative conceptual-theoretical approach. Through strict inclusion and exclusion criteria screening techniques from the SINTA, Google Scholar, and Garuda databases, 8 accredited national journal articles were selected and analyzed using content and thematic analysis. The findings confirm that the implementation of PAIKEM is consistently able to transform passive teaching patterns into an active and meaningful process of assimilating science knowledge. The joyful approach in this strategy is proven effective in reducing academic anxiety while stimulating intrinsic motivation through the fulfillment of students' basic psychological needs. PAIKEM demonstrates an inclusive level of scalability to be applied to the concrete operational stage of students across various grade levels. In conclusion, the PAIKEM strategy is highly relevant in transforming basic science learning, where its effectiveness heavily relies on the educator's proficiency in maintaining a pedagogical balance between joyful physical activities and scientific substance depth.